Help Others and Yourself Eventually: Exploring the Relationship between Help-Giving and Employee Creativity under the Model of Perspective Taking - Li, Si; Liao, Shudi (Frontiers in Psychology, 2017)
Although a plethora of studies have examined the antecedents of creativity, empirical studies exploring the role of individual behaviors in relation to creativity are relatively scarce. Drawing on the model of perspective taking, this study examines the relationship between help-giving during creative problem solving process and employee creativity. Specifically, we test perspective taking as an explanatory mechanism and propose organization-based self-esteem as the moderator. In a sample collected from a field survey of 247 supervisor-subordinate dyads from 2 large organizations in China at 3 time points, we find that help-giving during creative problem solving process positively related with perspective taking; perspective taking positively related with employees’ creativity; employees’ organization-based self-esteem strengthened the link between perspective taking and creativity; besides, there existed a moderated mediation effect. We conclude this paper with discussions on the implications for theory, research and practice.